Case Report: fNIRS-guided rehabilitation in refractory post-traumatic dysphagia - Wang, Xiaohan; Guo, Liying; Wang, Yanan; Ma, Wenlei; Wang, Lijin; Yan, Yanning; Yin, Yu (Frontiers in Rehabilitation Sciences, 2025)
BackgroundDysphagia is a common complication of severe traumatic brain injury (sTBI) and may persist despite standard treatment. For refractory cases, there appear to be no more effective therapeutic options available.Case informationA 15-year-old boy continued to suffer from severe dysphagia nine months after severe traumatic brain injury, remaining dependent on tracheostomy and nasogastric feeding. Prior interventions, including two botulinum toxin injections and a 35-day multimodal rehabilitation program, failed to yield meaningful improvement. At readmission, swallowing assessments showed profound impairment, malnutrition, and poor treatment tolerance. Functional near-infrared spectroscopy (fNIRS) was then applied to map cortical activation and guide targeted therapy. After 42 days, swallowing function improved significantly, with the Functional Oral Intake Scale (FOIS) rising from level I to VI and the Penetration-Aspiration Scale (PAS) decreasing from 8 to 2.ConclusionsThe therapeutic outcome of this case suggests that selecting training methods based on fNIRS-identified cortical activation can have a positive and significant impact on swallowing rehabilitation in patients with severe traumatic brain injury.